2022
DOI: 10.3389/fpubh.2022.1023010
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning models for predicting risk of depression in Korean college students: Identifying family and individual factors

Abstract: BackgroundDepression is one of the most prevalent mental illnesses among college students worldwide. Using the family triad dataset, this study investigated machine learning (ML) models to predict the risk of depression in college students and identify important family and individual factors.MethodsThis study predicted college students at risk of depression and identified significant family and individual factors in 171 family data (171 fathers, mothers, and college students). The prediction accuracy of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
0
6
2
Order By: Relevance
“…SVM has consistently been identified as a high-performing algorithm in predicting depression among students (see, e.g., 49 51 ). However, RF also emerged as the top-performing algorithm in some studies (see, e.g., 50 52 ), which contrasts with the present findings where it displayed some signs of overfitting and exhibited comparative lower performance. The observed overfitting in the RF algorithm in both classification and regression tasks within this study can be attributed to various factors.…”
Section: Discussioncontrasting
confidence: 99%
“…SVM has consistently been identified as a high-performing algorithm in predicting depression among students (see, e.g., 49 51 ). However, RF also emerged as the top-performing algorithm in some studies (see, e.g., 50 52 ), which contrasts with the present findings where it displayed some signs of overfitting and exhibited comparative lower performance. The observed overfitting in the RF algorithm in both classification and regression tasks within this study can be attributed to various factors.…”
Section: Discussioncontrasting
confidence: 99%
“…SVM has consistently been identified as a high-performing algorithm in predicting depression among students (see, e.g., Choudhury et al, 2019;Gil et al, 2022;Qasrawi et al, 2022). However, RF also emerged as the top-performing algorithm in some studies (see, e.g., Gil et al, 2022;Qasrawi et al 2022;Rois et al, 2021), which contrasts with the present findings where it examination of multi-versus univariate models revealed two dominant features (depression at T1 and anxiety), with the remaining features exhibiting limited significance. As for the discrepancies in algorithm performance between different studies, these may be ascribed to several factors.…”
Section: B Comparison Of Multivariate To Univariate Models In the Reg...contrasting
confidence: 88%
“…As for the ML algorithms performance in this study, both SVM/SVR and LogReg/RR demonstrated the best results in both classification and regression tasks. SVM has consistently been identified as a high-performing algorithm in predicting depression among students (see, e.g., Choudhury et al, 2019; Gil et al, 2022; Qasrawi et al, 2022). However, RF also emerged as the top-performing algorithm in some studies (see, e.g., Gil et al, 2022; Qasrawi et al 2022; Rois et al, 2021), which contrasts with the present findings where it displayed overfitting and exhibited comparative lower performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As AI rapidly transforms the landscape of medicine, academic research on the intersection of AI and college student mental health has significantly increased in recent years ( Gil et al, 2022 ; Wang, 2023 ). This necessitates a comprehensive review of the research trends in this field.…”
Section: Introductionmentioning
confidence: 99%